2017
DOI: 10.1017/pasa.2017.52
|View full text |Cite
|
Sign up to set email alerts
|

Super-AGB Stars and their Role as Electron Capture Supernova Progenitors

Abstract: We review the lives, deaths and nucleosynthetic signatures of intermediate-mass stars in the range ≈6-12 M , which form super-AGB stars near the end of their lives. The critical mass boundaries both between different types of massive white dwarfs (CO, CO-Ne, ONe), and between white dwarfs and supernovae, are examined along with the relative fraction of super-AGB stars that end life either as an ONe white dwarf or as a neutron star (or an ONeFe white dwarf), after undergoing an electron capture supernova event.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
193
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(206 citation statements)
references
References 262 publications
(607 reference statements)
3
193
3
Order By: Relevance
“…Lifetimes in the thermal-pulsing phase are short in SAGB stars (10 4−5 years; e.g. the review by Doherty et al 2017), but these lifetimes in combination with a MLR that could exceed 10 −5 M ⊙ yr −1 indicate that the initial mass of MSX SMC 055 could very well be up to 1 M ⊙ larger than its current mass. García-Hernández et al (2009) observed this and other massive AGB star candidates in the MCs in the optical at high spectral resolution.…”
Section: A Super-agb Star Candidatementioning
confidence: 99%
“…Lifetimes in the thermal-pulsing phase are short in SAGB stars (10 4−5 years; e.g. the review by Doherty et al 2017), but these lifetimes in combination with a MLR that could exceed 10 −5 M ⊙ yr −1 indicate that the initial mass of MSX SMC 055 could very well be up to 1 M ⊙ larger than its current mass. García-Hernández et al (2009) observed this and other massive AGB star candidates in the MCs in the optical at high spectral resolution.…”
Section: A Super-agb Star Candidatementioning
confidence: 99%
“…Super AGB stars ignite carbon in their cores, leaving behind an ONe white dwarf (Siess 2007), though some super AGB stars may ultimately explode as electron-capture SNe (e.g., Doherty et al 2015Doherty et al , 2017.…”
Section: Super Agb Starsmentioning
confidence: 99%
“…Importantly, our measurement resolves the last remaining nuclear physics uncertainty in the final evolution of degenerate oxygen-neon stellar cores, allowing future studies to address the critical role of convection, which at present is poorly understood. Stars of 7-11 solar masses (M ) are prevalent in the Galaxy, their birth and death rate comparable to that of all heavier stars combined [1]. Yet, the ultimate fate of such "intermediate-mass stars" remains uncertain.…”
mentioning
confidence: 99%